Optimalisasi Penjualan Toko Sembako Dengan Metode Linear Programming (Studi Kasus: Toko Pede) - Capriyansyah, Rizky Jaya; Haludin, Guntur; Ardana, Rizky Mulya; Zhorif, Rozaan; Putra, Bintang Adi; Rasendrya, Rizkhiar Zaki (Peneliti.net, 2024)
Optimal sales is the main goal in a business, which is to achieve sales goals. SME staple food store is a store engaged in selling basic necessities. SME staple food stores were established in 2016 selling various household needs. Using linear programming, this research seeks to identify the best product combination for achieving maximum outcomes. Linear programming, the technique utilized in this study, has potential applications in the sales household needs using a simplex model using a data processing application with Qm For Windows to get the best answer and finally make some money. Optimal sales achieved by SMEs were demonstrated by the findings staple food stores were Rp. 9,750,000 and 12kg LPG Gas as many as 150 tubes, 3 kg LPG Gas as many as 690 tubes, Mineral Gallons as much as 1200 gallons, and Eggs as much as 225 kg. SME staple food stores sell various kinds of household that are primary, secondary and tertiary needs. SME staple food stores sell approximately 200 kinds of goods. SME staple food stores have 10 best selling items, but we only focus on 4 products, namely, LPG Gas, Eggs, and Gallons which provide 70% of profit contribution.